Biossensor impedimétrico contendo a lectina ConBr para detecção de carboidratos - Nobrega, Francisco Alekson Chaves (2019)
The ConBr lectin, extracted from seeds of the Canavalia brasiliensis beans, is a protein capable of specifically and reversibly binding to the glucose and mannose carbohydrates. The immobilization of such lectin on a modified electrode can be an interesting strategy for the development of biosensors with high selectivity for these sugars. Therefore, the objective of this work is to develop and to evaluate an impedimetric biosensor for glucose and mannose detection, which is based on the immobilization of ConBr on self-assembled monolayers (SAM) of the compound 4,4'-biphenyldithiol (HS2BP) on gold electrode. The biosensor was prepared from the immersion of a previously cleaned gold electrode with a known electrochemically active area in a solution containing 10 mmol L–1 HS2BP in acetone for 1 h for SAM Au/HS2BP formation. Then, the Au/HS2BP electrode was immersed in 10 nmol L–1 ConBr solution in tris-HCl buffer for 1 h, thus the Au/HS2BP/ConBr biosensor was obtained. Electrochemical Impedance and Cyclic Voltammetry using the redox [Fe(CN)6]3–/4– (1.0 mmol L–1) as probe molecules were used to characterize the biosensor fabrication and detection of carbohydrates in solution. By Linear Scan Voltammetry it was determined the amount of adsorbed (Γ) HS2BP molecules on surface as 3.03×10–10 mol cm-2 which is consistent with a monolayer. The surface pKa value of the HS2BP species was also determined by voltammetry as 6.0. The charge-transfer resistance (RCT) values between the Au/HS2BP/ConBr electrode and the probe molecules, calculated from electrochemical impedance results, showed a linear relationship with the concentration (from 25 to 125 nmol L–1) of mannose or glucose in the medium. Thus, the detection limit of the biosensor was calculated as 0.73 and 0.07 nmol L–1 for glucose and mannose, respectively. In addition, the biosensor when stored under suitable conditions (4oC in Tris-HCl buffer) showed good stability and reproducibility for more than three weeks.